Model test papers in agriculture - Brajendra...et.al. (New Delhi : Sharma publications & Distributors, 2012)
General agriculture is a vast and still growing. Keeping abreast with important outlines, requires a thorough coverage of many a subjects. Questions from basics of general science to below ground science carefully woven into molecular breeding sciences of plants spreading by wings of insects statistically aim to bring success to examines of diverse examinations.
Keywords: Agriculture -- Guide -- Competitive Examination